Thermophysical Characterization of Ionic Liquids Based on the Perfluorobutanesulfonate Anion: Experimental and Soft‐SAFT Modeling Results1. Issue 15 (21st June 2017) - Pereiro, Ana B.; Llovell, Fèlix; Araújo, João M. M.; Santos, Andreia S. S.; Rebelo, Luís Paulo N.; Piñeiro, Manuel M.; Vega, Lourdes F.
Abstract: Fluorinated ionic liquids (FILs) exhibit complex molecular behavior, where three different nanodomains (polar, hydrogenated nonpolar, and fluorinated nonpolar) have been identified by molecular simulations. Given the high number of possible anion/cation combinations, a theoretical tool able to describe the thermophysical properties of these compounds in a systematic, rapid, and accurate manner is highly desirable. We present here a combined experimental–theoretical methodology to obtain the phase, interface, and transport properties of the 1‐alkyl‐3‐methylimidazolium perfluorobutanesulfonate ([C n C1 Im][C4 F9 SO3 ]) family. In addition to providing new experimental data, an extended version of the Statistical Associating Fluid Theory (soft‐SAFT) is used to describe the physicochemical behavior of the [C n C1 Im][C4 F9 SO3 ] family. A mesoscopic molecular model is built based on the analysis of the chemical structures of these FILs, and supported by quantum chemical calculations to study the charge distribution of the anion, where only the basic physical features are considered. The resulting molecular parameters are related to the molecular weight, providing the basis for thermophysical predictions of similar compounds. The theory is also able to predict the minimum in the surface tension versus the length of the hydrogenated alkyl chain, experimentally found at n =8. The viscosity parameters are also in agreement with the free‐volume calculations obtained from experiments. Abstract : Predictable properties : Given the high number of possible anion/cation combinations of fluorinated ionic liquids (FILs), a theoretical tool able to describe the thermophysical properties of these compounds in a systematic, rapid, and accurate manner is highly desirable. Thus, a combined experimental–theoretical methodology based on the soft‐SAFT molecular model has been used to obtain the phase, interface, and transport properties of the [C n C1 Im][C4 F9 SO3 ] family of FILs and to predict the surface tension minimum.